Adsorber heat exchanger using Al-fumarate beads for heat-pump applications – a transport study. (24th November 2020) - Farrusseng, David; Daniel, Cécile; Hamill, Conor; Casaban, Jose; Didriksen, Terje; Blom, Richard; Velte, Andreas; Fueldner, Gerrit; Gantenbein, Paul; Persdorf, Patrick; Daguenet-Frick, Xavier; Meunier, Francis
Abstract : This paper describes the cost-efficient and scalable synthesis and shaping processes of Al(OH)-fumarate beads of various sizes appropriate for use in water Adsorption Heat-Pumps (AHPs). Abstract : Metal–Organic Frameworks (MOFs), thanks to their type V water adsorption isotherms ("S-Shape") and large water capacities, are considered as potential breakthrough adsorbents for heat-pump applications. In particular, Al(OH)-fumarate could enable efficient regeneration at a lower temperature than silica-gel which would allow us to address the conversion of waste heat at low temperature such as found in data centers. Despite its greater adsorption capacity features, heat and mass transport limitations could jeopardize the potential performance of Al(OH)-fumarate. Heat and mass transport depend on the size of the bodies (mm range), their packing and on the pore structures, i.e. macro–mesopore volumes and sizes. This paper describes the cost-efficient and scalable synthesis and shaping processes of Al(OH)-fumarate beads of various sizes appropriate for use in water Adsorption Heat-Pumps (AHPs). The objective was to study transport limitations ( i.e. mass and heat) in practical e beads which meet mechanical stability requirements. Dynamic data at the grain scale was obtained by the Large Temperature Jump method while dynamic data at the adsorber scale was obtained on a heat exchanger filled with more than 1 kg of Al(OH)-fumarate beads. Whereas the binder content had little impact on mass and heat transfer in this study, we found that Knudsen diffusion in mesopores of the grain may be the main limiting factor at the grain scale. At the adsorber scale, heat-transfer within the bed packing as well as to the heat exchanger is likely responsible for the slow adsorption and desorption kinetics which have been observed for very low desorption temperature. Finally, the dynamic aspects of the observed water adsorption isotherm shift with temperature are discussed in light of reported reversible structure modification upon temperature triggered water adsorption–desorption.